The shallow arch: A step towards bridges styling in the early 19th century. (15th July 2018) - Serrano-López, R.; Urruchi-Rojo, J.R.; Martínez-Martínez, J.A.
Highlights: The arch bridges shape evolution is analyzed in function of the rise-to-span ratio. Some influent variables to maximum stress in a masonry bridge are analyzed. The influence of compacted soil backfill at spandrels is studied. The variation of ultimate load in a multi-span arch is analyzed using different designs. Abstract: Several formulations for masonry arches were appearing since 18th century, mostly based on the acquired experience in bridge construction. That led to a generalized use of shallow arch. The innovations supposed an evolution in the shape of masonry arch bridges, at the expense of increasing the thickness of voussoirs and vault. The question is: were the mentioned changes related with a clear structural improvement? Or were they mainly aesthetic or fashion-driven changes? This paper tries to give deeper insight and response this query by making a comparison among different formulations, and analyzing the rise to span ratio and backfill influences in both ultimate load capacity and maximum stress. Moreover, a multi-span arch bridge is analyzed, performing a comparison among different typological possibilities, and using examples of real structures in the Carrión river basin (Spain).